Atividade de Patógenos Causadores da BVD, Neosporose e IBR em Rebanhos Leiteiros - FELIPPIN, Rodrigo R. (2016)
The experiment was conducted with the objective of evaluating the behavior of endemic diseases, which affect the sanity of dairy herds, directly influencing the productive and reproductive results of the animals. Blood samples of 216 animals were evaluated for BoHV-1 Ac, BVD Ac, BVD Ag and Neospora Caninum Ac, from 3 properties of the southern Minas Gerais, which belonged to the Dutch, Jersey and Girolando breeds. The animals were separated and distributed into groups according to the category, age, open days and test titration result. In order to identify the prevalence of these pathogens in the studied properties, the activity of these agents was monitored by the individual serology of the animals. For the BVD virus, 38.4% of the animals were positive, showing a significant effect (P <0.0001), with variation in viral activity ranging from 58% and 44.8% to 9.7%. Searching for viral fragments (antigen), which demonstrates the presence of the BVD virus, only 1 animal from the property with a higher incidence of positive serologies was diagnosed positive. This animal was later confirmed as permanently infected (PI), a condition in which the immune system identifies the virus as a particle of the organism itself, serving as a source of transmission for the herd. For the protozoan Neospora Caninum, 27.3% of the animals were seropositive, and again the property effect (P <0.01) showed higher prevalences (35% and 40%) in the same properties with high BVD indexes. The interpretation of the results obtained for IBR, however, should consider the behavior of a herpes virus, where, once infected, the animal remains infected for life. The indexes found (P <0.001) of positive prevalence ranged from 85.0% to 51.6%. We conclude that these infectious agents act on the reproduction of each property, varying according to the flow of the animals, animal concentration and sanitary aspects. And that the implementation of a health program based on the serological diagnosis is feasible and possible to be incorporated into the routine of the properties. For the BVD to identify the presence of PI animals is fundamental to maintain the health of the herd.